A framework for automating e-government services based on artificial intelligence - Ali Sarabadani; Mahrdad Saffarie; Kheirollah RahseparFard (مدیریت مهندسی و رایانش نرم)
Electronic government refers to the provision of continuous government information and services to people through the Internet or other digital methods. The electronic government revolution has the ability to transform the public sector and re-establish the relationship between the government and citizens, a revolution that would have been almost ineffective without the element called artificial intelligence. One of the biggest developments of the last few years can be called the launch of e-government by artificial intelligence all over the world. In this paper, we address the challenges of e-government systems and propose a framework that uses artificial intelligence. In the next step, we present an intelligent e-government database architecture that supports the development and implementation of e-government artificial intelligence applications. The main goal is to use reliable artificial intelligence techniques in advancing the current state of e-government. Services to minimize processing time, reduce costs and improve citizen satisfaction.